EFEKTIVITAS MODEL PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR IPA MATERI RANTAI MAKANAN SISWA KELAS 5 SD NEGERI 2 BANDAR SAKTI - Kurniawan, Pandi Fajar; Puspita, Ryan Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to test the effectiveness of the Differentiated Learning Model on the learning outcomes of fifth grade students of SD Negeri 2 Bandar Sakti in the Natural Sciences (IPA) subject of the Food Chain. Differentiated Learning is applied in an effort to accommodate the diversity of learning needs of students. This study uses the Pretest-Posttest Control Group Design. The research sample consisted of two fifth grade classes of SD Negeri 2 Bandar Sakti which were randomly selected, namely one class as an experimental group that received Learning with the Differentiated Model, and one class as a Control Group that received Conventional Learning. The data collection instrument was in the form of a validated multiple-choice Learning Outcome Test. Learning outcome data were analyzed using the Independent Samples T-test Statistical Test to determine significant differences between the learning outcomes of the two groups after being given treatment. The results of the study showed that there were significant differences in the learning outcomes of the food chain material between students who learned using the Differentiated Learning Model and students who learned using the Conventional Learning Model. The experimental group showed a higher increase in Learning Outcomes compared to the control group. Thus, it can be concluded that the Differentiated Learning Model is Effective in improving the Science Learning Outcomes of the Food Chain material for grade V students at SD Negeri 2 Bandar Sakti.